O efeito do treino de autocontrole sobre o desempenho de escolha no Jogo da Partilha - Fidelis, Dafne Pavanelli (Universidade Federal de São Carlos, 2019)
All behavior implies choice and every choice, like all behavior, is installed and maintained by the consequences it produces in the environment. Choices are at the basis of what decision-making behaviors are. Self-control, for example, refers to the choice of a stimulus that produces delayed reinforcement, but of greater magnitude, as opposed to choice by a stimulus that produces an immediate reinforcement but of a smaller magnitude, known as impulsivity. Much of what is meant by social behavior can also be understood under the approach of behavior of choice, such as generosity, selfishness, and altruism. Generosity has been defined as a systematic pattern of choices that benefits the other in the same way that it benefits the one who makes the choice. Selfishness, on the other hand, has been defined as a pattern of choices that benefits the one making the choice and less the other, and altruism, a pattern of choices that benefits the other and nothing, or almost nothing, the one that makes the choice. To study the different patterns of choice the area has used an instrument known as Sharing Game. Studies that have used this game to study the phenomena of generosity and self-control have shown that such processes can be influenced by variables such as differences between genders, cultures and cost of response. However, no study was conducted to investigate whether a participant who had a selfish response pattern, after undergoing self-control training, could have his pattern of selfish responses modified by a pattern of optimized responses in the Sharing Game. The goal of these studies was to evaluate the effect of a self-control training on the emission of optimized responses in the Sharing Game in participants with typical (Study 1) and atypical (Study 2) development. In Study 1, initially the participants were submitted to the Sharing Game and the temporary discount task. If they had their response patterns classified as selfish and impulsive, they underwent a self-controlled response training, which involved a simple discrimination (TDS), reinforcement quantity training (TDR) and reinforcement delay training (TAR). Participants were then submitted to the abrupt reinforcement delay condition (AAA) and later to a high preference activity self-control training (CEAP). Finally, participants were again submitted to the Sharing Game to identify whether self-control training had an effect on the emission of optimized responses. The same procedures were applied in Study 2, however, initially it was tested if the participant presented discrimination of the greater relation between the Numerals and later, he was submitted to all sequence of procedures of the previous study. The results of study 1 demonstrated that the participant, who initially presented a pattern of selfish responses in the Sharing Game and an impulsive pattern in the task of temporal discount, after being submitted to the training of self-control, started to chose significantly more optimized responses in the Sharing Game. The results obtained in study 2, with participants with atypical development, demonstrated that the participants did not present the necessary prerequisites to verify if a pattern of selfish responses in the Sharing Game and impulsive in the task of temporal discount can be altered after the participants are submitted to self-control training
The effect of self control training on the performance of choosing in the Sharing Game
Keywords: Autocontrole; Comportamento social; Jogo da Partilha; Self-control; Social behavior; Sharing Game; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL::PROCESSOS DE APRENDIZAGEM, MEMORIA E MOTIVACAO